Seletividade de agrotóxicos utilizados na cultura do mamoeiro sobre o predador Neoseiulus idaeus denmark & muma (acari: phytoseiidae) - Silva, Valesca Batista da (Universidade Federal Rural do Semi-Árido, 2017)
The importance of fruticulture with emphasis on papaya production in Brazil can be seen by the position of the country in the world ranking, which it’s placed as the second largest producer of papaya in the world. However, the great amount of diseases and arthropods pests that affect this fruit orchards daily are still one of the major barrier to its success. Among these, the spider mite Tetranychus urticae Koch (Acari: Tetranychidae) has excelled for causing countless direct and indirect loss to papaya crops. Its control has been made through the excessive use of agrochemicals, resulting in disastrous consequences for the environment and human health. Therefore, studies have been carried out in the search of alternative controls to the chemical to suppress this pest, and in this context, the predatory mite Neoseiulus idaeus Denmark & Muma (Acari: Phytoseiidae) appears as a potential biological control agent for the spider mite. Its use in consortium with the chemical control must occur through the knowledge about the products to be used so that these are selective to this phytoseiidae. Thus, three pesticide toxicity experiments on adults of N. idaeus were set up to test the selectivity of eighteen agricultural pesticides, which are generally used in papaya orchards. The entirely randomized design was used and each treatment consisted of 25 repetitions that that were exposed to contamination by direct spraying and were evaluated daily in order to verify the mortality or not of the contaminated individuals. The obtained data were subjected to Kruskall-Wallis (KW) test through the R software and the products used were classified according to its toxicity to the predator and according to the norms of the International Organization for Biological Control (IOBC/WPRS). All fungicides, the insecticide Thiamethoxan and the acaricide Hexythiazox were innocuous while Acetamiprid and Bifenthrin were considered harmful.
Monografia
Keywords: Manejo integrado de pragas; Ácaro predador; Controle biológico; Integrated pest management; Biological control; Biological control; CIENCIAS AGRARIAS::AGRONOMIA